A kind of microwave-absorbing printing paste, flexible lightweight composite microwave-absorbing fabric and preparation method and application thereof

Through screen printing technology, the graphene/MXene/Fe3O4 composite slurry is coated on the surface of the fabric, which solves the problem of difficult control of the immersion time and impregnation agent concentration in the preparation of composite wave absorbing fabrics, and achieves efficient, green and environmentally friendly flexible and lightweight absorption Wave fabric preparation has excellent wave absorption performance and wide application prospects.

CN116497615BActive Publication Date: 2024-12-24QINGDAO UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310568637.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-19
Publication Date
2024-12-24
Estimated Expiration
2043-05-19

AI Technical Summary

Technical Problem

In the existing methods for preparing composite wave absorbing fabrics, the impregnation time and impregnation agent concentration are difficult to accurately control, resulting in cumbersome operation and environmental pollution, which limits the green and environmental protection and industrial development of the materials.

Method used

The graphene/MXene/Fe3O4 composite slurry was prepared by screen printing technology, and the fabric surface was coated through a one-step method, combining the synergistic effects of graphene, MXene and Fe3O4 to adjust impedance matching and enhance the absorption performance.

Benefits of technology

It realizes the efficient preparation of flexible lightweight composite wave absorbing fabrics, with excellent wave absorbing performance, antibacterial properties and green environmental protection. It is suitable for electromagnetic shielding, radar stealth and other fields, simplifying the operation process and reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116497615B_ABST
    Figure CN116497615B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of electromagnetic wave absorbing materials, in particular to a wave absorbing printing paste, a flexible and lightweight composite wave absorbing fabric and a preparation method and application thereof. By adopting a screen printing method, a graphene, MXene and Fe3O4 composite slurry is scraped on the surface of an aramid nonwoven fabric, and a soft and lightweight graphene@MXene@Fe3O4 composite wave absorbing fabric with antibacterial properties is prepared by a simple one-step method, wherein graphene provides dielectric loss, and MXene constructs a conductive network on the interlaced fibers to adjust impedance matching. At the same time, the magnetic material Fe3O4 is introduced to further improve impedance matching and increase magnetic loss. In addition, there are abundant interfaces between the above three materials and between the materials and the fabric, which will produce interface polarization, further enhance the wave absorbing performance, and are more green and environmentally friendly, easy to operate, and provide a new idea for the green industrial production of flexible wearable composite wave absorbing fabrics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electromagnetic wave absorbing materials, in particular to a wave absorbing printing paste, a flexible light composite wave absorbing fabric and a preparation method and application thereof. Background Art

[0002] Electromagnetic wave pollution has become another major source of pollution in the 21st century after air pollution, water pollution, and light pollution. It not only affects the operation of precision instruments but also threatens human health. In addition, with the in-depth development of precision-guided weapons, wearable stealth materials have become a key research project for the armaments of various countries. Therefore, the development of textile composite absorbing materials has important significance and application value for the performance improvement of electromagnetic protection materials and national defense security.

[0003] CN106374233A A high-efficiency wave-absorbing composite material, using oxalate as a coordination agent and crown ether as a coating agent, double crystallizing ferric chloride, aluminum chloride and nickel chloride to obtain a mixed magnetic material, and mixing with graphene powder, an adhesive, a coupling agent and a dispersant to form a suspension dispersion, and then pulling and constant temperature to obtain the wave-absorbing material. The method of the invention is simple, the process conditions are mild, the production cost is low, the material structure is stable, it has not been damaged by high temperature, the magnetism is intact, the overall performance is good, the surface density is low, and the absorption frequency band is wide.

[0004] At present, the preparation of composite absorbing fabrics usually adopts the impregnation method. For example, Wang et al. constructed a MXene / Ni chain / ZnO array hybrid nanostructure on cotton fabric using the impregnation method. The impedance matching, reflection loss and effective absorption bandwidth can be regulated by the number of Ni impregnations. The minimum RL value of the fabric reaches -35.1dB at 8.3GHz and the thickness is 2.8mm. Wang et al. prepared carbon fiber fabrics by electrospinning, connected them with Ni Fe layered double hydroxide (Ni Fe LDH) / MXene derivatives by impregnation, and prepared composite absorbing fabrics. When the thickness is 2.5mm, the minimum reflection loss is -58.0dB and the effective absorption bandwidth (RL<-10dB, f e ) reached 7.0GHz. Zhang et al. prepared cellulose nanofiber (CF) fabric by electrospinning technology, and then deposited conductive polyaniline (PANI) on the CF surface by impregnation method. The minimum reflection loss value was -49.24dB, and the effective absorption bandwidth reached 6.90GHz.

[0005] The above-mentioned prior art proposes to prepare the absorbing material by the impregnation method, but the impregnation time is one of the important factors affecting the analysis results of the impregnation method, but it is difficult to control the accuracy of the impregnation time. Different samples and impregnants may require different impregnation times, and the length of the impregnation time is also affected by the experience and skills of the operator. Therefore, it is necessary to conduct multiple experiments to determine the optimal impregnation time, and often a certain impregnation technique is required to achieve the purpose of uniform impregnation. Furthermore, the concentration of the impregnant is another important factor affecting the analysis results of the impregnation method, but it is difficult to accurately control the concentration of the impregnant. Different samples and impregnants may require different impregnant concentrations, and the concentration of the impregnant is also affected by the experimental environment and the operating process. Therefore, it is necessary to conduct multiple experiments to determine the optimal concentration of the impregnant. In addition, a long drying time is required for drying, so the operation is relatively cumbersome. More importantly, the wastewater discharged after impregnation will pollute the environment, and the wastewater discharge system will also waste energy. Therefore, it is of great significance to develop a more green and environmentally friendly, easy-to-operate composite absorbing fabric preparation system.

[0006] Graphene materials are widely used in the field of microwave absorption due to their ultra-light weight, huge specific surface area and excellent mechanical properties. Wei et al. partially reduced graphene oxide (GO) and loaded magnetic quantum dots (MQDs) by a one-step pyrolysis method, and prepared three new composite materials of MQDs (Fe, Fe3O4, Fe3C) embedded in partially reduced graphene oxide (P-rGO). The study found that the loading of MQDs on a single carbon material increased the magnetic loss mechanism and improved the impedance matching and attenuation capabilities. The samples prepared under 800℃ pyrolysis conditions can obtain 5.59GHz broadband electromagnetic wave absorption at an ultra-thin thickness of 1.7mm. Zhong et al. developed a double salt template method to prepare N, S co-doped graphite carbon nanoframes (GF) anchored on graphene sheets (GS). The study found that N, S co-doping would cause dipole polarization loss and enhance the microwave absorption performance of the material. At a low filler ratio of 10wt%, the minimum reflection loss of N, S-GF / GS at a thickness of 2.3mm was -45.64dB, and the effective absorption bandwidth at 1.5mm was 4.35GHz. From the above, it can be seen that although graphene has very excellent performance, its single dielectric loss will cause an imbalance in impedance matching, so that electromagnetic waves cannot enter the material for absorption, so it is often necessary to add other materials to adjust the impedance matching to achieve excellent absorption performance. MXene has high conductivity, rich defects and surface active groups, and is a commonly used two-dimensional material in the field of microwave absorption. Wang et al. designed and prepared a bionic sea urchin-like Ti3C2T x@ZnO hollow microspheres, with strong reflection loss of -57.4dB and wide effective absorption band of 6.56GHz. Li et al. constructed an ultralight magnetic composite foam by electrostatic self-assembly of MXene on the surface of graphene skeleton and subsequent hydrothermal anchoring of flower-shaped FeS clusters. The minimum reflection loss reached -47.17dB at a thickness of 4.78mm, and the corresponding effective absorption bandwidth was as high as 6.15GHz. As a good magnetic absorber, Fe3O4 has attracted extensive attention due to its unique magnetic properties and semi-metallic characteristics. However, a single magnetic loss cannot achieve the purpose of effectively absorbing electromagnetic waves. Summary of the invention

[0007] In view of the deficiencies in the above-mentioned prior art, an absorbing printing paste, a flexible lightweight composite absorbing fabric, and a preparation method and application thereof are provided. A soft and lightweight composite absorbing fabric with antibacterial properties is prepared by a simple one-step method. The fabric has excellent absorbing performance, is more environmentally friendly, and is easy to operate. It has very broad application prospects in the field of flexible multifunctional absorbing materials.

[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is a microwave absorbing printing paste, which is obtained by blending graphene slurry, MXene dispersion, Fe3O4 dispersion and thickener, wherein the actual solid content of graphene, MXene, Fe3O4 and thickener is 45-75%, 3-8%, 20%-45% and 1-3% respectively; the graphene slurry includes 100-200g graphene filter cake, 200-300g diethylene glycol butyl ether, and 50-100g aqueous acrylic emulsion or aqueous polyurethane emulsion, the Fe3O4 is a dispersion obtained by chemical reaction of 4-6g FeCl3·6H2O, 1-3g FeCl2·4H2O, 30-50mL water and 15-20ml 0.08mol NaOH solution, and the concentration of the MXene solution is 1-10mg / mL.

[0009] The flexible light composite absorbing fabric is prepared by coating the printing paste described in claim 1 on the surface of the fabric through screen printing.

[0010] The thickness of the above-mentioned flexible lightweight composite absorbing fabric is 0.2-1.5 mm.

[0011] The above-mentioned flexible lightweight composite absorbing fabric has a reflectivity peak value of -20--47dB at 12.3GHz, and an effective absorption bandwidth of 1-5GHz.

[0012] The antibacterial rates of the above-mentioned flexible light composite wave-absorbing fabric on Staphylococcus aureus and Escherichia coli are both above 99%.

[0013] The above-mentioned flexible lightweight composite absorbing fabric includes an aramid non-woven fabric, and the conductive graphene and MXene loaded aramid fiber surface are interwoven to form a conductive network, causing conductive loss. At the same time, in the alternating electric field, the defects of graphene and MXene can generate dipoles, thereby inducing dipole polarization. In addition, there are abundant interfaces between graphene, MXene and Fe3O4, which can cause interface polarization and further enhance the absorbing performance. Secondly, the introduction of magnetic material Fe3O4 further increases the magnetic loss and improves impedance matching. The magnetic loss of Fe3O4 mainly attenuates electromagnetic waves through eddy current loss, natural resonance and exchange resonance. Finally, the electromagnetic wave is incident on the surface of the GMF fabric, and will be reflected and scattered multiple times between the composite slurry and the fabric and inside the staggered aramid fibers. In addition, multiple reflection effects can also be generated between the multi-layer structure of MXene, which can further enhance the loss of electromagnetic waves of the composite fabric. The limiting oxygen index of the absorbing fabric is above 28%, and the vertical combustion afterburning and smoldering time are both less than 3s.

[0014] The above-mentioned flexible lightweight composite absorbing fabric can be folded and bent at will, and the gram weight is 100-500g / cm 2 .

[0015] The method for preparing the above-mentioned flexible lightweight composite absorbing fabric comprises the following steps:

[0016] (1) preparing graphene slurry: mixing 100-200 g of cake-shaped graphene with 200-300 g of diethylene glycol butyl ether, mechanically stirring at 2000-4000 r / min for 1-1.5 h, adding 50-100 g of aqueous acrylic emulsion, and stirring at 500-1000 r / min for 30-60 min to obtain graphene slurry;

[0017] (2) Preparation of Fe3O4 dispersion: 4-6g FeCl3·6H2O and 1-3g FeCl2·4H2O are completely dissolved in 30-50mL water, and 15-25mL 0.08mol NaOH solution is slowly added dropwise at 60-80°C and 400-500r / min of mechanical stirring until the solution changes from brown to black, react for 50-60min, wash several times until neutral, and calibrate the concentration;

[0018] (3) Preparation of composite fabric: Take 10-12 g of the graphene slurry prepared in step (1), add 15-20 mL of MXene with a concentration of 2-5 mg / mL and 5-15 mL of Fe3O4 dispersion with a concentration of 20-30 mg / mL, stir evenly at 400-500 r / min, add 0.5-1 g of thickener, stir at 500-1000 r / min for 20-60 min to obtain a printing paste, treat the fabric with a vacuum plasma treatment machine for 5 min, and then apply the printing paste on the surface of the fabric by screen printing to obtain a graphene / MXene / Fe3O4 composite fabric.

[0019] In the above-mentioned method for preparing the flexible lightweight composite absorbing fabric, in the step (3), the screen printing process steps are: vehicle speed 15-25m / min, pressure 2.5-5pa, drying temperature 110-180°C, slurry viscosity 8000-12000mPa·s, printing plate mesh 100-200 mesh, slurry circulation width 600-900mm.

[0020] Flexible lightweight composite absorbing fabrics are widely used in electromagnetic shielding, radar stealth and electromagnetic pulse protection materials, as well as in clothing, tents, tarpaulins and camouflage nets.

[0021] The beneficial effects of the invention of a wave-absorbing printing paste, a flexible and lightweight composite wave-absorbing fabric, and a preparation method and application thereof are that currently, flexible and lightweight composite wave-absorbing fabrics often adopt a multiple impregnation method, which pollutes the environment and has cumbersome and complicated operation steps, limiting the development of environmentally friendly and industrialized preparation of composite wave-absorbing fabrics. The invention adopts a screen printing method to scrape the graphene, MXene and Fe3O4 composite slurry on the surface of the fabric, and adopts a simple one-step method to prepare a soft and lightweight graphene@MXene@Fe3O4 composite wave-absorbing fabric with antibacterial properties, wherein graphene provides dielectric loss, and MXene constructs a conductive network on the interlaced fibers to adjust impedance matching. At the same time, the magnetic material Fe3O4 is introduced to further improve impedance matching and increase magnetic loss. In addition, there are abundant interfaces between the above three materials and between the materials and the fabrics, which will produce interface polarization and further enhance the absorbing performance, so that GMF can achieve a minimum reflection loss of -47dB at an ultra-thin thickness of 1.5mm. Not only that, this fabric also has excellent properties of antibacterial, softness and lightness. More importantly, soft and lightweight composite absorbing fabrics have great application potential in electromagnetic shielding, radar stealth and electromagnetic pulse protection. The preparation process of GMF is more environmentally friendly and easy to operate than the impregnation method currently used by most absorbing fabrics, which provides a new idea for the green industrial production of flexible wearable composite absorbing fabrics. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The present invention is a process flow chart of preparing a flexible and lightweight composite absorbing fabric;

[0023] Figure 2 The SEM images, EDS images, XRD images, XPS images, and FTIR images of the fabrics are shown;

[0024] Figure 3 It is the electromagnetic parameter diagram of composite absorbing fabric;

[0025] Figure 4 This is the wave absorbing performance diagram of the composite wave absorbing fabric;

[0026] Figure 5 This is a diagram of the wave absorption mechanism. DETAILED DESCRIPTION

[0027] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0028] A wave absorbing printing paste is obtained by blending graphene slurry, MXene dispersion, Fe3O4 dispersion and thickener, wherein the actual solid contents of graphene, MXene, Fe3O4 and thickener are 45-75%, 3-8%, 20%-45% and 1-3% respectively; the graphene slurry comprises 100-200g of graphene filter cake, 200-300g of diethylene glycol butyl ether and 50-100g of aqueous acrylic emulsion or aqueous polyurethane emulsion; the Fe3O4 is a dispersion obtained by chemical reaction of 4-6g of FeCl3·6H2O, 1-3g of FeCl2·4H2O, 30-50mL of water and 15-20ml of 0.08mol NaOH solution; the concentration of the MXene solution is 1-10mg / mL.

[0029] The flexible light composite absorbing fabric is prepared by coating the printing paste described in claim 1 on the surface of the fabric through screen printing.

[0030] The above-mentioned flexible lightweight composite absorbing fabric has a thickness of 0.2-1.5 mm. The fabric can be folded and bent at will, and the gram weight is 100-500 g / cm 2 .

[0031] The reflectivity peak is -20--47dB at 12.3GHz, and its effective absorption bandwidth is 1-5GHz. Its antibacterial rate against Staphylococcus aureus and Escherichia coli is above 99%.

[0032] Example 1

[0033] The method for preparing the above-mentioned flexible lightweight composite absorbing fabric comprises the following steps:

[0034] (1) preparing graphene slurry: 100 g of cake-shaped graphene was mixed with 200 g of diethylene glycol butyl ether, and mechanically stirred at 2000 r / min for 1 h, then 50 g of aqueous acrylic emulsion was added, and stirred at 500 r / min for 30 min to obtain graphene slurry;

[0035] (2) Preparation of Fe3O4 dispersion: 4 g FeCl3·6H2O and 1 g FeCl2·4H2O were completely dissolved in 30 mL water, and 15 mL 0.08 mol NaOH solution was slowly added dropwise at 60°C and 400 r / min under mechanical stirring until the solution changed from brown to black. The mixture was reacted for 50 min, washed several times until neutral, and the concentration was calibrated.

[0036] (3) Preparation of composite fabric: 10 g of the graphene slurry prepared in step (1) was added with 15 mL of 2 mg / mL MXene and 5 mL of 20 mg / mL Fe3O4 dispersion, and stirred at 400 r / min for uniform mixing. 0.5 g of thickener was added, and stirred at 500 r / min for 20 min to obtain a printing paste. The aramid non-woven fabric was treated with a vacuum plasma treatment machine for 5 min, and the printing paste was coated on the fabric surface by screen printing to obtain a graphene / MXene / Fe3O4 composite fabric.

[0037] In the step (3), the process steps of screen printing are: vehicle speed 15m / min, pressure 2.5Pa, drying temperature 110°C, slurry viscosity 8000mPa·s, printing plate mesh 100 mesh, and slurry circulation width 600mm.

[0038] Example 2

[0039] The same parts of this embodiment as those of the first embodiment are not described in detail. The difference between the present embodiment and the first embodiment is that the method for preparing the above-mentioned flexible lightweight composite absorbing fabric comprises the following steps:

[0040] (1) Preparation of graphene slurry: 165 g of cake-shaped graphene was mixed with 295 g of diethylene glycol butyl ether, and mechanically stirred at 3500 r / min for 1.01 h, and then 51 g of aqueous acrylic emulsion was added, and stirred at 700 r / min for 31 min to obtain graphene slurry;

[0041] (2) Preparation of Fe3O4 dispersion: 5.4 g FeCl3·6H2O and 2 g FeCl2·4H2O were completely dissolved in 31 mL water, and 20 mL 0.08 mol NaOH solution was slowly added dropwise at 79°C and 450 r / min mechanical stirring until the solution changed from brown to black. The mixture was reacted for 51 min, washed several times until neutral, and the concentration was calibrated.

[0042] (3) Preparation of composite fabric: 11 g of the graphene slurry prepared in step (1) was added with 16.5 mL of MXene with a concentration of 2-5 mg / mL and 14 mL of Fe3O4 dispersion with a concentration of 28 mg / mL, and stirred at 450 r / min for uniformity. 0.51 g of thickener was added, and stirred at 700 r / min for 30 min to obtain a printing paste. After treating the aramid non-woven fabric with a vacuum plasma treatment machine for 5 min, the printing paste was coated on the fabric surface by screen printing to obtain a graphene / MXene / Fe3O4 composite fabric.

[0043] In the step (3), the process steps of screen printing are: vehicle speed 16m / min, pressure 3pa, drying temperature 130°C, slurry viscosity 9000mPa·s, printing plate mesh 150 mesh, and slurry circulation width 700mm.

[0044] Example 3

[0045] The same parts of this embodiment as those of the first embodiment are not described in detail. The difference between the present embodiment and the first embodiment is that the method for preparing the above-mentioned flexible lightweight composite absorbing fabric comprises the following steps:

[0046] (1) Preparation of graphene slurry: 200 g of cake-shaped graphene was mixed with 300 g of diethylene glycol butyl ether, and mechanically stirred at 4000 r / min for 1.5 h, and then 100 g of aqueous acrylic emulsion was added, and stirred at 1000 r / min for 60 min to obtain graphene slurry;

[0047] (2) Preparation of Fe3O4 dispersion: 6 g FeCl3·6H2O and 3 g FeCl2·4H2O were completely dissolved in 50 mL water. 25 mL 0.08 mol NaOH solution was slowly added dropwise at 80°C and 500 r / min mechanical stirring until the solution changed from brown to black. The mixture was reacted for 60 min, washed several times until neutral, and the concentration was calibrated.

[0048] (3) Preparation of composite fabric: 12 g of the graphene slurry prepared in step (1) was added with 20 mL of 5 mg / mL MXene and 15 mL of 30 mg / mL Fe3O4 dispersion, and stirred at 500 r / min. 1 g of thickener was added, and stirred at 1000 r / min for 60 min to obtain a printing paste. The aramid non-woven fabric was treated with a vacuum plasma treatment machine for 5 min, and the printing paste was coated on the fabric surface by screen printing to obtain a graphene / MXene / Fe3O4 composite fabric.

[0049] In the step (3), the process steps of screen printing are: vehicle speed 25m / min, pressure 5pa, drying temperature 180°C, slurry viscosity 12000mPa·s, printing plate mesh 200 mesh, and slurry circulation width 900mm.

[0050] Example 4

[0051] The same parts as those in Example 1 are not described in detail here. The difference is that when the ratios of graphene, MXene, Fe3O4 and thickener are 60%, 5% and 33%, 2% respectively, the effect is optimal, the minimum reflection loss of the absorbing fabric at 12.3 GHz is as high as -47 dB, and the effective absorption bandwidth is 3 GHz (9.4-12.4 GHz).

[0052] Example 5

[0053] The same parts as those in Example 1 are not described in detail. The difference is that the fabric includes an aramid nonwoven fabric, and the conductive graphene and the surface of the aramid fiber loaded with MXene are interwoven to form a conductive network, which causes conductive loss. At the same time, in the alternating electric field, the defects of graphene and MXene can generate dipoles, thereby inducing dipole polarization. In addition, there are abundant interfaces between graphene, MXene and Fe3O4, which can cause interface polarization and further enhance the wave absorption performance. Secondly, the introduction of the magnetic material Fe3O4 further increases the magnetic loss and improves the impedance matching. The magnetic loss of Fe3O4 mainly attenuates the electromagnetic wave through eddy current loss, natural resonance and exchange resonance. Finally, the electromagnetic wave is incident on the surface of the GMF fabric, and multiple reflections and scatterings will be performed between the composite slurry and the fabric and inside the staggered aramid fibers. In addition, multiple reflection effects can also be generated between the multilayer structure of MXene, which can further enhance the loss of electromagnetic waves of the composite fabric. The limiting oxygen index of the wave absorbing fabric is above 28%, and the vertical combustion afterburning and smoldering time are both less than 3s.

[0054] Generally speaking, excellent microwave absorption performance often requires the synergistic effect of dielectric loss and magnetic loss to achieve. A single loss mechanism may cause poor impedance matching. In this study, graphene is used to provide dielectric loss, MXene is used to adjust impedance matching, and magnetic Fe3O4 is introduced to further adjust impedance matching and provide magnetic loss. After the three are physically mixed, they are loaded on aramid fabric to obtain a flexible and efficient microwave absorbing fabric. In order to study the microwave absorption performance of the composite absorbing fabric, the fabric was cut into a rectangle of 25mm*50mm, clamped in an X-band (8.2GHz-12.4GHz) waveguide fixture, and its electromagnetic parameters were evaluated using a vector network analyzer.

[0055] Figure 3(af) are the electromagnetic parameters of the three samples G, GM, and GMF in the X-band. According to Maxwell's electromagnetic field theory, the absorbing performance of the composite absorbing material mainly depends on the complex dielectric constant (ε r =ε′-jε″) and complex magnetic permeability (μ r =μ′-jμ″), where the real part (ε′) and imaginary part (ε″) of the complex dielectric constant represent the energy storage and loss of electric energy, respectively, and the real part (μ′) and imaginary part (μ″) of the complex magnetic permeability represent the energy storage and loss of magnetic energy, respectively. At the same time, the tangent value of the dielectric constant (tgδε=ε″ / ε) and the tangent value of the magnetic permeability (tgδμ=μ″ / μ′) are used to characterize the material's loss capacity for microwaves. By Figure 3 (a) It can be seen that with the increase of frequency, the ε′ of the G sample decreases, which is a typical dispersion phenomenon. Overall, with the addition of MXene and Fe3O4, the ε′ of the sample shows a significant downward trend. This is because after the introduction of MXene, the difference in conductivity between graphene and MXene causes a competition between polarization loss and conductive loss, resulting in a decrease in the overall conductivity of the composite material. Therefore, the composite fabric's ability to store electrical energy is weakened. However, this weakening can optimize impedance matching and allow more electromagnetic waves to enter the interior of the material. At the same time, with the addition of MXene and Fe3O4, the ε″ of the sample decreases. According to the free electron theory, the decrease in ε″ is mainly caused by the decrease in conductivity, that is, the decrease in the composite material's ability to lose electrical energy. In addition, the sample's ε′ and ε″ have some weak resonant peaks, which are mainly caused by the defects on the MXene causing the asymmetric distribution of charges and inducing dipole polarization. The dielectric loss characteristics of the sample are further discussed. Generally speaking, the larger the value of tgδε, the better the dielectric loss performance of the material, due to Figure 3 (c) It can be seen that the dielectric loss performance of the sample is G>GM>GMF. The reason is that after the introduction of MXene, the conductive loss generated by graphene competes with the dielectric loss generated by MXene. The further introduction of magnetic material Fe3O4 will increase the surface area of ​​the material load, resulting in a weakening of the dielectric loss capacity. Figure 3 (df) shows that μ′, μ″ and tgδμ of the three fabrics show similar trends. At the same time, μ″ and tgδμ of GMF are significantly higher than those of G and GM, indicating that GMF has higher magnetic loss. Usually, magnetic loss mainly comes from ferromagnetic resonance, hysteresis loss, domain wall resonance and eddy current loss. Among them, hysteresis loss is relatively weak in the microwave field and can be ignored. In addition, domain wall resonance mainly occurs in the MHz range, not the GHz range, so it is not considered. Therefore, the magnetic loss of the sample mainly comes from ferromagnetic resonance and eddy current loss. At the same time, the mechanism of magnetic loss can be explained by the formula C0=μ″(μ′) -2 f -1To explain, if C0 is a straight line that has nothing to do with the change of frequency, then the magnetic loss will be completely realized by eddy current loss. Obviously, if Figure 3 As shown in (h), the C0 of GMF changes with the frequency, indicating that its magnetic loss mechanism is not only eddy current loss, but also includes natural resonance and exchange resonance.

[0056] Impedance matching (Z) and attenuation constant (α) are the two most critical parameters for discussing wave absorption performance. The value of impedance matching determines whether electromagnetic waves can enter the material without being reflected, and the value of the attenuation constant determines the material's attenuation performance for electromagnetic waves. The two together determine the material's wave absorption performance. They are calculated using the following two formulas:

[0057]

[0058]

[0059] Where Z is the normalized impedance, Z in is the input impedance of the fabric, Z0 is the free space impedance, h is Planck's constant, f is the frequency, d is the thickness of the material, and c is the speed of light. Generally, the closer the value of the normalized impedance Z is to 1, the better the impedance matching performance of the material, and the more electromagnetic waves can enter the interior of the material without being reflected. Figure 3 (i) It can be seen that the Z value of GMF is closest to 1, and the Z value of G is farthest from 1, which proves that GMF has the best impedance matching performance. The reason is that MXene and Fe3O4 can effectively match the impedance, allowing more electromagnetic waves to enter the interior of the material. Figure 3 (g) It can be seen that the α values ​​of the three fabrics increase first and then decrease with the increase of frequency, but the peak values ​​of G and GM appear near 10.5GHz, while the peak value of GMF appears near 12.0GHz, which shows that the magnetic material has a certain influence on the frequency range of electromagnetic wave absorption by the composite material. And the order of α is: G>GMF>GM. The reason why G has a larger α value is that it has a higher conductive loss, and the reason why GMF has a larger α value than GM is that it introduces magnetic loss.

[0060] According to the transmission line theory, the absorption performance of composite fabrics to electromagnetic waves can be expressed by reflection loss (RL). The value of RL is calculated by the following formula:

[0061]

[0062] Generally speaking, when RL is less than -10dB, it means that 90% of the electromagnetic waves are absorbed. Figure 4 (a, d, g) shows that G does not have effective wave absorption performance in the X-band. Figure 4 (b) It can be seen that when the thickness of GM is 2mm, the minimum reflection loss at 10.9GHz reaches -33.9dB, and the effective absorption bandwidth (EAB) is 3.5GHz (8.9-12.4GHz) Figure 4 (e,h). With the addition of Fe3O4, the wave absorption performance of the fabric is further improved. Figure 4 As shown in (c), when the thickness is only 1.5 mm, the minimum reflection loss of GMF at 12.3 GHz is as high as -47 dB. Figure 4 (f,i) shows that the effective absorption bandwidth of the fabric is 3GHz (9.4-12.4GHz), and at the same time, the minimum reflection loss of the GMF fabric at 8.5GHz reaches -23dB at a thickness of 2mm. In general, the performance of GMF is much greater than that of G and GM fabrics, both in terms of fabric thickness and the value of minimum reflection loss. This can be explained by the synergistic effect of the dielectric loss provided by graphene and MXene and the magnetic loss of Fe3O4, as well as the interface polarization generated by the rich interface between the three.

[0063] Based on the above discussion, the wave absorption mechanism of GMF may be as follows Figure 5 As shown. First, dielectric loss and conductive loss play a major role in the process of electromagnetic wave attenuation. Among them, the conductive graphene and MXene-loaded aramid fiber surface interweave to form a conductive network, causing conductive loss. At the same time, in the alternating electric field, the defects of graphene and MXene can produce dipoles, thereby inducing dipole polarization. In addition, there are abundant interfaces between graphene, MXene and Fe3O4, which can cause interface polarization and further enhance the wave absorption performance. Secondly, the introduction of magnetic material Fe3O4 further increases the magnetic loss and improves impedance matching. The magnetic loss of Fe3O4 mainly attenuates electromagnetic waves through eddy current loss, natural resonance and exchange resonance. Finally, the electromagnetic wave is incident on the surface of the GMF fabric, and multiple reflections and scatterings will be carried out between the composite slurry and the fabric and inside the staggered aramid fibers. In addition, multiple reflection effects can also be produced between the multilayer structure of MXene, which can further enhance the loss of electromagnetic waves of the composite fabric. In summary, the excellent wave-absorbing performance of GMF fabric comes from the excellent impedance matching of graphene, MXene and Fe3O4 and the synergistic effect of different loss mechanisms.

[0064] Flexible lightweight composite absorbing fabrics are widely used in electromagnetic shielding, radar stealth and electromagnetic pulse protection materials, as well as in clothing, tents, tarpaulins and camouflage nets.

[0065] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by ordinary technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.

Claims

1. A wave-absorbing printing paste, characterized in that: The wave-absorbing printing paste is obtained by blending graphene slurry, MXene dispersion, Fe3O4 dispersion and thickener, wherein the actual solid contents of graphene, MXene, Fe3O4 and thickener are 45-75%, 3-8%, 20%-45% and 1-3% respectively; the graphene slurry comprises 100-200g of graphene filter cake, 200-300g of diethylene glycol butyl ether, and 50-100g of aqueous acrylic emulsion or aqueous polyurethane emulsion, the Fe3O4 is a dispersion obtained by chemical reaction of 4-6gFeCl3·6H2O, 1-3g FeCl2·4H2O, 30-50mL water and 15-20ml 0.08mol NaOH solution, and the concentration of the MXene solution is 1-10mg / mL.

2. Flexible lightweight composite absorbing fabric, characterized in that: The printing paste according to claim 1 is coated on the surface of fabric by screen printing.

3. The flexible lightweight composite absorbing fabric according to claim 2, characterized in that: Its thickness is 0.2-1.5mm.

4. The flexible lightweight composite absorbing fabric according to claim 3 is characterized in that: The reflectivity peak is -20 - -47dB at 12.3GHz, and its effective absorption bandwidth is 1-5GHz.

5. The flexible lightweight composite absorbing fabric according to claim 4 is characterized in that: Its antibacterial rates against Staphylococcus aureus and Escherichia coli are both above 99%.

6. The flexible lightweight composite absorbing fabric according to claim 5, characterized in that: The fabric includes aramid non-woven fabric, which is interwoven by conductive graphene and aramid fiber surfaces loaded with MXene to form a conductive network, causing conductive loss. At the same time, in an alternating electric field, defects in graphene and MXene can generate dipoles, thereby inducing dipole polarization. In addition, there are abundant interfaces between graphene, MXene and Fe3O4, which can cause interface polarization and further enhance the wave absorbing performance. Secondly, the introduction of magnetic material Fe3O4 further increases magnetic loss and improves impedance matching. The magnetic loss of Fe3O4 mainly attenuates electromagnetic waves through eddy current loss, natural resonance and exchange resonance. Finally, the electromagnetic wave is incident on the surface of the GMF fabric, and will be reflected and scattered multiple times between the composite slurry and the fabric and inside the staggered aramid fibers. In addition, multiple reflection effects can also be generated between the multi-layer structure of MXene, which can further enhance the loss of electromagnetic waves of the composite fabric. The limiting oxygen index of the absorbing fabric is above 28%, and the vertical combustion afterburning and smoldering times are both less than 3s.

7. The flexible lightweight composite absorbing fabric according to claim 6 is characterized in that: The fabric can be folded and bent at will, and the weight is 100-500g / cm².

8. A method for preparing the flexible lightweight composite absorbing fabric according to any one of claims 2 to 7, characterized in that: The steps include: (1) Preparation of graphene slurry: 100-200 g of cake-shaped graphene was mixed with 200-300 g of diethylene glycol butyl ether, and mechanically stirred at 2000-4000 r / min for 1-1.5 h, and then 50-100 g of aqueous acrylic emulsion was added, and stirred at 500-1000 r / min for 30-60 min to obtain graphene slurry; (2) Prepare Fe3O4 dispersion: 4-6g FeCl3·6H2O and 1-3g FeCl2·4H2O are completely dissolved in 30-50mL water. Slowly add 15-25mL 0.08 mol NaOH solution under mechanical stirring at 60-80℃ and 400-500r / min until the solution changes from brown to black. React for 50-60min, wash several times until neutral, and calibrate the concentration. (3) Preparation of composite fabric: 10-12 g of the graphene slurry prepared in step (1) is added with 15-20 mL of a MXene solution having a concentration of 2-5 mg / mL and 5-15 mL of a Fe3O4 dispersion having a concentration of 20-30 mg / mL, and stirred at 400-500 r / min to obtain a printing paste. 0.5-1 g of a thickener is added, and stirred at 500-1000 r / min for 20-60 min to obtain a printing paste. The fabric is treated with a vacuum plasma treatment machine for 5 min, and the printing paste is coated on the fabric surface by screen printing to obtain a graphene / MXene / Fe3O4 composite fabric.

9. The method for preparing the flexible lightweight composite absorbing fabric according to claim 8, characterized in that: In step (3), the screen printing process steps are: vehicle speed 15-25 m / min, pressure 2.5-5 Pa, drying temperature 110-180 ° C, slurry viscosity 8000-12000 mPa·s, printing plate mesh 100-200 mesh, slurry circulation width 600-900 mm.